“Weathering” and Age Patterns of Allostatic Load Scores Among Blacks and Whites in the United States - Geronimus, Arline T. (© American Journal of Public Health 2006, 2006)
Objectives. We considered whether US Blacks experience early health deterioration, as measured across biological indicators of repeated exposure and adaptation to stressors. Methods. Using National Health and Nutrition Examination Survey data, we examined allostatic load scores for adults aged 18–64 years. We estimated probability of a high score by age, race, gender, and poverty status and Blacks’ odds of having a high score relative to Whites’ odds. Results. Blacks had higher scores than did Whites and had a greater probability of a high score at all ages, particularly at 35–64 years. Racial differences were not explained by poverty. Poor and nonpoor Black women had the highest and second highest probability of high allostatic load scores, respectively, and the highest excess scores compared with their male or White counterparts. Conclusions. We found evidence that racial inequalities in health exist across a range of biological systems among adults and are not explained by racial differences in poverty. The weathering effects of living in a race-conscious society may be greatest among those Blacks most likely to engage in high-effort coping.